Mumps Vaccines: Current Challenges and Future Prospects - Almansour, Iman (Frontiers in Microbiology, 2020)
Five decades have passed since the first mumps vaccine was licensed. Over this period, a resurgence of mumps infections have been recorded worldwide. Although global mumps infections have been controlled through vaccination, outbreaks are still on the rise, including in populations with high vaccination coverage. Several epidemiological studies suggest this infectious virus continues to be a worldwide public health threat. The development and deployment of an improved, prophylactic mumps vaccine that provides long-lasting protection is indeed a priority. The purpose of this review is to provide an immuno-biological perspective on mumps vaccines. Here, we review the virology of mumps, licensed mumps vaccines, and the typical immune responses elicited following mumps vaccination. Furthermore, we discuss the limitations and challenges of the currently licensed mumps vaccines and provide strategies for the development of an improved mumps vaccine.